Exploring inventory management practices in the Omani SME’S - Al Shahri, Ahmed Ali; Mohd. Yusuff, Rosnah (2005)
Good inventory management system has always been important in the workings of an effective supply chain. This research investigates the practice of supply chain management in the Omani SME’s with a focus on the techniques adopted by Omani industries in managing their inventory as well as the mechanism adopted to cope with demand requirements. The recent developments in the international business arena have driven firms all over the world to adopt new strategies for better product quality with low cost to ensure customer satisfaction. The traditional thinking of keeping inventory has become obsolete in the new business environment where zero inventories are the preferred practice. Additionally, Oman 2020 vision requires companies to move up to the next level where they will be able to compete on the international stage in order to achieve the promising objective, which is projected for the manufacturing sector to contribute 15% to GDP. The research has been conducted using a survey questionnaire, which has been designed to best capture the various inventory and demand management techniques that best describe the mechanisms applied to balance the supply and demand chain. The results indicate the majority of sales for the majority of respondents occur at the end of each month. The majority of respondent companies carry a high level of inventory to protect against forecast uncertainties and the fear of losing customer. Additionally, the average lead time for domestic order span from one week and one month, which is another reason for building up inventories. Moreover, 36 percent of respondents indicate a make to order inventory policy for their finished goods. The implementation of advanced technologies that link customers and supplier such as ERP and EDI is not existent.